Pediatric Endoscopic Pilonidal Sinus Treatment (PEPSiT) in Children With Pilonidal Sinus Disease: Tips and Tricks and New Structurated Protocol - Esposito, Ciro; Mendoza-Sagaon, Mario; Del Conte, Fulvia; Cerulo, Mariapina; Coppola, Vincenzo; Esposito, Giovanni; Cortese, Giuseppe; Crocetto, Felice; Montaruli, Ernesto; Escolino, Maria (Frontiers in Pediatrics, 2020)
Background: The advent of pediatric endoscopic pilonidal sinus treatment (PEPSiT) has dramatically changed the surgical management of pilonidal sinus disease (PSD) in children and adolescents. This study aimed to report the outcome of our new structurated protocol, including PEPSiT, laser epilation and oxygen-enriched oil-based gel dressing, for treatment of PSD in pediatric patients and describe tips and tricks of the technique. Methods: We retrospectively reviewed the data of 127 pediatric patients, who underwent PEPSiT for PSD in our institutions over a 36-month period. All patients received laser epilation (LE) before and after surgery. Postoperative dressing was performed using silver sulfadiazine spray and in the last 18 months oxygen-enriched oil-based gel. We divided the patients in two groups according to the protocol adopted: G1 (laser + oxygen-enriched oil-based gel dressing) included 72 patients and G2 (laser + silver sulfadiazine spray dressing) included 55 patients. The two groups were compared regarding success rate, recurrence, wound infection rate, wound healing time, postoperative outcome, time to full daily activities and patient satisfaction. Results: No difference emerged between the two groups regarding the average operative time, the average postoperative pain score, the average analgesic requirement, the average hospitalization and the average time to full daily activities (p=0.33). No intra- or postoperative complications including wound infection occurred in both groups. The patients required an average number of 7 LE sessions (range 4-10) to achieve complete hair removal. The overall success rate was significantly higher in G1 (n=71, 98.6%) compared with G2 (n=50, 90.9%) [p=0.001]. The recurrence rate was also significantly lower in G1 (n=1, 1.4%) compared with G2 (n=5, 9%) [p=0.001]. Furthermore, G1 reported a faster wound healing (average 21 days) compared with G2 (average 29 days) [p=0.001] and a higher patient satisfaction score (average 4.9) compared with G2 (average 4.2) [p=0.001]. Conclusions: Based upon our experience, PEPSiT may be considered the standard of care for surgical treatment of PSD in children and adolescents. Our new structurated protocol consisting of pre-operative LE, PEPSiT and postoperative wound management with oxygen-enriched oil-based gel dressing and LE, allowed to achieve an excellent outcome, with a success rate > 98%.